A revision of the South African endemic humicolous beetle genus Discozantaena Perkins and Balfour-Browne (Coleoptera: Hydraenidae) - Perkins, Philip D. (Zootaxa, 2005)
The South African endemic humicolous beetle genus Discozantaena Perkins and Balfour-Browne is revised, based of the study of 1,735 specimens. Ten new species are described: D. brevicollis, (S. Cape Mt., Helderfontein S.), D. drakensbergensis (Lesotho: Drakensberg, Sani Pass Valley), D.endroedyi (Cape-Cederberg, jeep track, 32° 28' S, 19° 14' E), D. galea (Cape Province, Swartberg Pass, 33° 54' S–22° 01' E), D. karroo (Cape Province, Little Karroo, Raubenheimer Dam, 33° 25' S, 22° 19' E), D. leleupi (Cape Province, Muizenberg), D. ovata (SW Cape, Groot Toren farm, 31° 20' S, 19° 44' E), D. sepiola (S. Cape, Harkerville Forest, 34° 4' S, 23° 10' E), D. sequentia (Cape-Cederberg, jeep track, 32° 28' S, 19° 14' E), and D. tibiovela (Natal, 75km WSW Estcourt, Cathedral Peaks Forest Station). A key to the 11 known species is given. High resolution digital images of all holotypes are presented (Zootaxa online version in color), the male genitalia are illustrated, and geographic distributions are mapped. The vast majority of specimens were collected by sifting litter, especially marsh shore litter. Four of the species are flightless, the wings being reduced to small lobes. One species has both normal and reduced winged individuals.